Evaluation of cardiac abnormalities by Doppler echocardiography in a large nationwide multicentric cohort of patients with systemic sclerosis. Issue 1 (31st January 2007) - de Groote, P; Gressin, V; Hachulla, E; Carpentier, P; Guillevin, L; Kahan, A; Cabane, J; Francès, C; Lamblin, N; Diot, E; Patat, F; Sibilia, J; et al.
Abstract : Objectives: There is increasing concern about heart and pulmonary vascular involvement in systemic sclerosis (SSc). One of the most severe complications of SSc is pulmonary arterial hypertension (PAH). There has been an increased awareness of left ventricular (LV) diastolic abnormalities in SSc patients. However, previous studies have generally been conducted in small populations. The aims of this study were to prospectively screen for PAH and to describe echocardiographic parameters in a large group of SSc patients. Methods: This prospective study was conducted in 21 centres for SSc in France. Patients without severe pulmonary function abnormalities, severe cardiac disease and known PAH underwent Doppler echocardiography performed by a reference cardiologist. Results: Of the 570 patients evaluated, PAH was suspected in 33 patients and was confirmed in 18 by right heart catheterisation. LV systolic dysfunction was rare (1.4%). LV hypertrophy was found in 22.6%, with LV diastolic dysfunction in 17.7%. These LV abnormalities were influenced by age, gender and blood pressure. We identified a small group of 21 patients with a restrictive mitral flow pattern in the absence of any other cardiopulmonary diseases, suggesting a specific cardiac involvement in SSc. Conclusions: Left and right heart diseases, including PAH, LV hypertrophy and diastolic dysfunction, are common in SSc. However, a small subset of patients without any cardiac or pulmonary diseases have a restrictive mitral flow pattern that could be due to primary cardiac involvement of SSc. The prognostic implications of the LV abnormalities will be evaluated in the 3-year follow-up of this cohort.